Different times, same story: Native forest loss and landscape homogenization in three physiographical areas of south-central of Chile. (June 2015) - Miranda, Alejandro; Altamirano, Adison; Cayuela, Luis; Pincheira, Francoise; Lara, Antonio
Abstract: Temperate forest represents the smallest area among the main world's forest biomes, but is one of those most threatened by forest loss. Chile contains most of the temperate forest in South America and more than half of the temperate forest in the southern hemisphere. Chilean temperate forest is considered to be one of the world's biodiversity hotspots. In this study we assessed the rate of land use and land cover (LULC) change over time, identified the main LULCs replacing native forest, and described how changes have evolved in contrasting physiographical conditions and through different historical phases of the landscape over the last 40 years. To achieve this, we analysed LULC change with particular focus on forest cover in three areas representing different physiographical conditions and histories of human occupation in the Araucanía Region of Chile, namely the Central Valley, the Coastal range, and the Andean range. We found substantial differences in temporal and intra-regional patterns of forest loss and LULC change. In the Central Valley, forest loss started long ago, and the area occupied by native forest nowadays is less than 5% of the landscape. In the Coastal range, rapid land cover change has taken place since 1973, with an increasing rate of forest loss over time. We detected a similar but less intense pattern in the forests of the Andean range. Overall, the general pattern points to a process of landscape homogenization in all three physiographical areas. Exotic tree plantations have spread over large geographical areas, becoming the dominant land cover. Land cover change in the Araucanía Region reflects a model of change in which areas with better environmental conditions and accessibility are occupied first for productive activities. As the availability of suitable areas for the expansion of productive activities diminishes, these activities start to move into physiographical areas which were previously "protected" by adverse environmental conditions or poor accessibility. This model of production growth could lead to the complete deforestation of areas outside national protected areas, and other areas which still remain inaccessible due to technological restrictions on exploitation. Highlights: We investigated the heterogeneity of LUCC and forest loss pattern in space and time. The general pattern pointed to a process of landscape homogenization. Exotic tree plantation was the dominant land cover in large areas of region. This model could lead to the complete deforestation outside of protected areas.